Peroral endoscopic myotomy for management of cricopharyngeal bars (CP-POEM): a retrospective evaluation - Al Ghamdi, Sarah S.; Bejjani, Michael; Hernández Mondragón, Oscar V.; Parsa, Nasim; Yousaf, Muhammad N.; Aghaie Meybodi, Mohammad; Ghandour, Bachir; Krustri, Chonlada; Phalanusitthepha, Chainarong; Ngamruengphong, Saowanee; Nieto, Jose M.; Khashab, Mouen A. (Endoscopy, 2021)
Background Cricopharyngeal bars (CPBs) are a unique etiology of oropharyngeal dysphagia. Symptomatic patients are managed with endoscopic dilation or surgical myotomy. Cricopharyngeal peroral endoscopic myotomy (CP-POEM) is an emerging technique for the management of dysphagia due to CPBs. This study evaluated technical success, clinical success, adverse events, and long-term recurrence following CP-POEM.Methods Consecutive patients who underwent POEM for management of CPBs between May 2015 and December 2020 at four tertiary care centers were included. Primary outcome was clinical success (defined as improvement of dysphagia score to ≤ 1). Secondary outcomes were technical success, rate and severity of adverse events, procedure duration, and symptom recurrence. Results 27 patients (mean age 69 years; 10 female) underwent CP-POEM during the study period. The most common presenting symptoms at the time of index procedure were dysphagia (26; 96.3 %) and regurgitation (20; 74.1 %). Clinical and technical success were achieved in all patients. Mild/moderate adverse events occurred in two patients (7.4 %). CP-POEM significantly reduced the median dysphagia score. Conclusions CP-POEM was a safe and effective treatment for symptomatic CPBs. Although symptom recurrence was low, long-term outcome data are needed. CP-POEM should be considered as a management option for symptomatic CPBs at centers with POEM expertise.